EVALUATION OF SERUM BETA-HYDROXYBUTYRATE LEVELS AS AN EARLY DIAGNOSTIC MARKER OF DIABETIC KETOACIDOSIS (Editora Impacto Científico, 2025)
Diabetic ketoacidosis (DKA) remains a life-threatening metabolic emergency when not diagnosed promptly. This integrative review, conducted in accordance with PRISMA-2020, evaluated the diagnostic accuracy, prognostic value and analytical requirements of blood β-hydroxybutyrate (BHB) in DKA management. PubMed, Scopus, Web of Science, Embase, SciELO and LILACS were searched (January 2015 – June 2025); 312 records were retrieved and 5 studies met the eligibility criteria. The corpus comprised accuracy trials, prospective and retrospective cohorts, and one systematic review, encompassing over 1 200 DKA episodes. Exploratory meta-aggregation of all five studies yielded a pooled AUC of 0.93 (95 % CI: 0.90–0.96) for the diagnostic threshold BHB ≥ 3 mmol/L, with overall sensitivity and specificity above 90 %. In paediatrics, a 5.3 mmol/L cut-off maximised specificity (96.4 %), whereas BHB < 1.5 mmol/L heralded biochemical resolution roughly 2.5 h earlier than anion-gap closure. Ambulatory evidence showed recurrent peaks ≥ 0.8 mmol/L doubled DKA risk in patients on SGLT2 inhibitors. Methodological studies recommended devices with coefficient of variation ≤ 9.1 % to safely track therapeutic declines of 0.5 mmol/L/h. BHB thus emerges as a reliable marker for diagnosis, follow-up and prevention of DKA, warranting replacement of urinary ketone testing and integration into telemonitoring programmes.